The Tech-Talk Balance: What Technical Interviewers Expect from Technical Candidates - Ford Robinson, Denae; Barik, Titus; Rand-Pickett, Leslie; Parnin, Chris (Proceedings of the IEEE ICSE 10th International Workshop on Cooperative and Human Aspects of Software Engineering (CHASE)., 2017)
Software engineer job candidates are not succeeding at technical interviews. Although candidates are able to answer technical questions, there is a mismatch of what candidates think interviewers assess versus what criteria is used in practice. This mismatch in expectations can cost candidates a job opportunity. To determine what criteria interviewers value, we conducted mock technical interviews with software engineer candidates at a university and collected evaluations from interviewers. We analyzed 70 interview evaluations from 9 software companies. Using a grounded theory approach, we compared interviewer interpretations of criteria including: performing a problem solving walkthrough, applying previous experience to problem solving, and the ability to engaging in conversation beyond writing code. From these findings, we provide implications on what candidates can expect to be evaluated on during technical interviews across companies, which can sometimes vary significantly.